Mexico : Financial Sector Assessment Program Update-Technical Note-Housing Finance. (IMF Staff Country Reports; Country Report ;, 2007)
This paper presents a technical note on Mexico's Financial Sector Assessment Program update. The Sociedad Hipotecaria Federal has successfully led a range of direct policy measures that have stimulated the development of the housing finance market. The government improved the legal environment for mortgage finance by passing reforms that reduced the average time to foreclosure from five years to two, by facilitating the reform of several state property registries and by facilitating mortgage securitization.